Advances in Soil Evaporation Physics—A Review. Issue 4 (24th May 2013) - Or, Dani; Lehmann, Peter; Shahraeeni, Ebrahim; Shokri, Nima
Abstract : Globally, evaporation consumes about 25% of solar energy input and is a key hydrologic driver with 60% of terrestrial precipitation returning to the atmosphere via evapotranspiration. Quantifying evaporation is important for assessing changes in hydrologic reservoirs and surface energy balance and for many industrial and engineering applications. Evaporation dynamics from porous media reflect interactions between internal liquid and vapor transport, energy input for phase change, and mass transfer across air boundary layer. We reviewed recent advances on resolving interactions between soil intrinsic properties and evaporation dynamics with emphasis on the roles of capillarity and wettability affecting liquid phase continuity and capillary driving forces that sustain Stage I evaporation. We show that soil water characteristics contain information for predicting the drying front depth and mass loss at the end of Stage I and thus derive predictions for regional‐scale evaporative water losses from soil textural maps. We discuss the formation of secondary drying front at the onset of Stage II evaporation and subsequent diffusion‐controlled dynamics. An important aspect for remote sensing and modeling involves nonlinear interactions between wet evaporating surfaces and air boundary layer above (evaporation rate is not proportional to surface water content). Using pore scale models of evaporating surfaces and vapor transport across air boundary layer, we examined the necessary conditions for maintenance of nearly constant evaporation while the surface gradually dries and the drying front recedes into the soil. These new insights could be used to improve boundary conditions for models that are based on surface water content to quantify evaporation rates.